Induction of stable mutants of Gliocladium virens by gamma-irradiation - A.N. MUKHOPADHYAY, P.K. MUKHERJEE* and (Indian Phytopathology, 2002)
Seven stable mutants of the biocontrol fungus Gliocladium virens have been generated by exposing the slant cultures to 125 k rad of gamma radiation. The mutants differed from the wild type strain in phenotype, growth rate, sporulation and antagonistic potential. One of the mutants, M-7, which produced profuse chlamydospores but no conidia was more aggressive than the wild type in antagonizing Sclerotium rolfsii and Fusarium oxysporum f.sp. ciceri in vitro. The usefulness of this mutant in ecological studies of G. virens has been discussed. All the mutants were insensitive to carboxin as the wild type strain, but none developed resistance to carbendazim,